Integrating Human Resources Management and Digital Competencies: A Strategic Approach in Higher Education - Teti Rohayati (AL-ISHLAH: Jurnal Pendidikan, 2024)
This paper explores the integration of Human Resources Management (HRM) and digital competencies as a strategic approach in higher education institutions. In this context, "digital competencies" refer to the ability of individuals to use digital technologies effectively and efficiently, encompassing a broad range of skills from basic digital literacy to advanced technical proficiencies. "Digital skills," on the other hand, are specific abilities required to operate digital tools and platforms, including data analysis, software usage, and online communication. Given the rapid advancement of digital technologies, higher education is at a pivotal juncture to embrace these changes to enhance administrative efficiency and academic excellence. The study utilizes a systematic literature review encompassing academic journals, industry reports, and policy documents to examine current practices and theoretical frameworks that align HRM with digital competencies within the sector. Key findings suggest that a strategic integration of digital skills in HRM not only optimizes operational processes but also fosters an environment conducive to digital learning and innovation. The research highlights several critical strategies, including the development of digital training programs for staff, the inclusion of digital competency frameworks in HR policies, and the strategic recruitment of tech-savvy personnel. Engagement with various stakeholders, such as faculty, administrative staff, and students, is crucial for the successful implementation of these strategies, ensuring that the institution's digital transformation aligns with the needs and expectations of its community. The paper concludes with recommendations for higher education leaders to cultivate a digitally competent workforce that can navigate and thrive in a technologically driven educational landscape. This approach is imperative for institutions aiming to maintain competitiveness and relevance in the digital age.